New winter wheat varieties for rigid forecrops developed by the FSBSI “ARC “Donskoy” - М. М. Ivanisov; D. M. Marchenko; I. A. Rybas’; A. V. Kirin (Зерновое хозяйство России)
The purpose of the current work was to evaluate new winter common wheat varieties developed by the FSBSI “ARC “Donskoy” according to the main economic and biological traits and properties. The competitive testing was carried out after two forecrops, such as maize for grain and sunflower. As initial forms when deve- loping new genotypes, there were taken the varieties of Zernograd breeding (‘Donskoy syurpriz’, ‘Rostovchanka 5’, ‘Spartak’,’ Don 107’) and of non-regional breeding (‘Zolushka’, ‘Sibirskaya niva’, ‘Irishka’) released in different years.The mean three-year productivity of new varieties (2021–2023) when sown after maize for grain varied from 7.77 t/ha (‘Volny Don’) to 8.32 t/ha (‘Flagman’), exceeding the standard variety ‘Don 107’ by 0.45–1.00 t/ha. When sown after sunflower it ranged from 6.64 t/ha (‘Volny Don’) to 6.82 t/ha (‘Donets’), with an increase relative to the standard variety from 0.45 to 0.63 t/ha. New winter common wheat genotypes produced higher yields relative to the standard variety due to various components of its elements. Maximum impact on productivity of the new winter common wheat varieties in 2021–2023 was made by 1000-grain weight (r = 0.54±0.37) and grain weight per ear (r = 0.77±0.26). New winter common wheat varieties had the same high and even higher frost resistance (72.2–84.5 %) as the highly frost- resistant standard variety ‘Don 107’ (74.1 %), short stemness (88.3–100 cm), lodging resistance (4.8–5.0 points). On an infectious background they were affected by brown rust and powdery mildew to a lesser extent compared to the standard variety ‘Don 107’. They formed good grain quality with protein (12.75–13.78 %), gluten (23.4–25.7 %), grain nature weight (787–812 g/l), hardiness (60–83 %).